Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the given compositions of functions, we need to follow step-by-step evaluations for each part:
Given:
[tex]\[ f(x) = 5 \sqrt{x} \][/tex]
[tex]\[ g(x) = 2x \][/tex]
Let's evaluate each composition one by one:
### (a) [tex]\((f \circ g)(4)\)[/tex]
The notation [tex]\((f \circ g)(4)\)[/tex] means we first apply [tex]\(g\)[/tex] to 4, and then apply [tex]\(f\)[/tex] to the result of [tex]\(g(4)\)[/tex].
1. Calculate [tex]\(g(4)\)[/tex]:
[tex]\[ g(4) = 2 \cdot 4 = 8 \][/tex]
2. Now, apply [tex]\(f\)[/tex] to the result of [tex]\(g(4)\)[/tex]:
[tex]\[ f(8) = 5 \sqrt{8} = 5 \sqrt{4 \cdot 2} = 5 \cdot 2 \sqrt{2} = 10 \sqrt{2} \][/tex]
Thus:
[tex]\[ (f \circ g)(4) = 10\sqrt{2} \][/tex]
### (b) [tex]\((g \circ f)(2)\)[/tex]
The notation [tex]\((g \circ f)(2)\)[/tex] means we first apply [tex]\(f\)[/tex] to 2, and then apply [tex]\(g\)[/tex] to the result of [tex]\(f(2)\)[/tex].
1. Calculate [tex]\(f(2)\)[/tex]:
[tex]\[ f(2) = 5 \sqrt{2} \][/tex]
2. Now, apply [tex]\(g\)[/tex] to the result of [tex]\(f(2)\)[/tex]:
[tex]\[ g(5 \sqrt{2}) = 2 \cdot 5 \sqrt{2} = 10 \sqrt{2} \][/tex]
Thus:
[tex]\[ (g \circ f)(2) = 10\sqrt{2} \][/tex]
### (c) [tex]\((f \circ f)(1)\)[/tex]
The notation [tex]\((f \circ f)(1)\)[/tex] means we first apply [tex]\(f\)[/tex] to 1, and then apply [tex]\(f\)[/tex] to the result of [tex]\(f(1)\)[/tex].
1. Calculate [tex]\(f(1)\)[/tex]:
[tex]\[ f(1) = 5 \sqrt{1} = 5 \][/tex]
2. Now, apply [tex]\(f\)[/tex] to the result of [tex]\(f(1)\)[/tex]:
[tex]\[ f(5) = 5 \sqrt{5} \][/tex]
Thus:
[tex]\[ (f \circ f)(1) = 5\sqrt{5} \][/tex]
### (d) [tex]\((g \circ g)(0)\)[/tex]
The notation [tex]\((g \circ g)(0)\)[/tex] means we first apply [tex]\(g\)[/tex] to 0, and then apply [tex]\(g\)[/tex] to the result of [tex]\(g(0)\)[/tex].
1. Calculate [tex]\(g(0)\)[/tex]:
[tex]\[ g(0) = 2 \cdot 0 = 0 \][/tex]
2. Now, apply [tex]\(g\)[/tex] to the result of [tex]\(g(0)\)[/tex]:
[tex]\[ g(0) = 2 \cdot 0 = 0 \][/tex]
Thus:
[tex]\[ (g \circ g)(0) = 0 \][/tex]
### Final Answers:
(a) [tex]\((f \circ g)(4) = 10\sqrt{2}\)[/tex]
(b) [tex]\((g \circ f)(2) = 10\sqrt{2}\)[/tex]
(c) [tex]\((f \circ f)(1) = 5\sqrt{5}\)[/tex]
(d) [tex]\((g \circ g)(0) = 0\)[/tex]
Given:
[tex]\[ f(x) = 5 \sqrt{x} \][/tex]
[tex]\[ g(x) = 2x \][/tex]
Let's evaluate each composition one by one:
### (a) [tex]\((f \circ g)(4)\)[/tex]
The notation [tex]\((f \circ g)(4)\)[/tex] means we first apply [tex]\(g\)[/tex] to 4, and then apply [tex]\(f\)[/tex] to the result of [tex]\(g(4)\)[/tex].
1. Calculate [tex]\(g(4)\)[/tex]:
[tex]\[ g(4) = 2 \cdot 4 = 8 \][/tex]
2. Now, apply [tex]\(f\)[/tex] to the result of [tex]\(g(4)\)[/tex]:
[tex]\[ f(8) = 5 \sqrt{8} = 5 \sqrt{4 \cdot 2} = 5 \cdot 2 \sqrt{2} = 10 \sqrt{2} \][/tex]
Thus:
[tex]\[ (f \circ g)(4) = 10\sqrt{2} \][/tex]
### (b) [tex]\((g \circ f)(2)\)[/tex]
The notation [tex]\((g \circ f)(2)\)[/tex] means we first apply [tex]\(f\)[/tex] to 2, and then apply [tex]\(g\)[/tex] to the result of [tex]\(f(2)\)[/tex].
1. Calculate [tex]\(f(2)\)[/tex]:
[tex]\[ f(2) = 5 \sqrt{2} \][/tex]
2. Now, apply [tex]\(g\)[/tex] to the result of [tex]\(f(2)\)[/tex]:
[tex]\[ g(5 \sqrt{2}) = 2 \cdot 5 \sqrt{2} = 10 \sqrt{2} \][/tex]
Thus:
[tex]\[ (g \circ f)(2) = 10\sqrt{2} \][/tex]
### (c) [tex]\((f \circ f)(1)\)[/tex]
The notation [tex]\((f \circ f)(1)\)[/tex] means we first apply [tex]\(f\)[/tex] to 1, and then apply [tex]\(f\)[/tex] to the result of [tex]\(f(1)\)[/tex].
1. Calculate [tex]\(f(1)\)[/tex]:
[tex]\[ f(1) = 5 \sqrt{1} = 5 \][/tex]
2. Now, apply [tex]\(f\)[/tex] to the result of [tex]\(f(1)\)[/tex]:
[tex]\[ f(5) = 5 \sqrt{5} \][/tex]
Thus:
[tex]\[ (f \circ f)(1) = 5\sqrt{5} \][/tex]
### (d) [tex]\((g \circ g)(0)\)[/tex]
The notation [tex]\((g \circ g)(0)\)[/tex] means we first apply [tex]\(g\)[/tex] to 0, and then apply [tex]\(g\)[/tex] to the result of [tex]\(g(0)\)[/tex].
1. Calculate [tex]\(g(0)\)[/tex]:
[tex]\[ g(0) = 2 \cdot 0 = 0 \][/tex]
2. Now, apply [tex]\(g\)[/tex] to the result of [tex]\(g(0)\)[/tex]:
[tex]\[ g(0) = 2 \cdot 0 = 0 \][/tex]
Thus:
[tex]\[ (g \circ g)(0) = 0 \][/tex]
### Final Answers:
(a) [tex]\((f \circ g)(4) = 10\sqrt{2}\)[/tex]
(b) [tex]\((g \circ f)(2) = 10\sqrt{2}\)[/tex]
(c) [tex]\((f \circ f)(1) = 5\sqrt{5}\)[/tex]
(d) [tex]\((g \circ g)(0) = 0\)[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.